Perlindungan Hukum terhadap Notaris dalam Pelaksanaan Jabatan Notaris Berdasarkan Teori Keseimbangan Berbasis Keadilan - Khairunnisa Noor Asufie; Ali Impron (Universitas Sebelas Maret, 2021)
Notary has two sides were attached, namely as an individual Indonesian citizens and public officials appointed by the competent authority. As a Notary as a holder of the office of Notary who performs duties as a public official appointed by an authorized official. Notary as an individual has a position as an Indonesian Citizen based on his personal identity as an Indonesian Citizen. The legal protection provided to the Notary is based on the position of the Notary as a public official appointed by an authorized public official, not legal protection as an individual Indonesian Citizen. Although the two are attached together but related to legal protection, there is a separation of the two positions. Legal protection of Notaries as individual Indonesian Citizens has been regulated by regulations already in Indonesia and related to the human rights of individual Indonesian Citizens while legal protection of Notaries as public officials is a topic of discussion that will be discussed further. Discuss the legal protection for Notaries in the performance of their duties by reviewing based on the principle of proportionality. Legal protection for Notaries in the performance of their office is now something important because many Notaries are criminalized in the performance of their office. The research method used for this research is normative research. This research is a prescriptive analysis. In this research, using the approach, the approach of legislation (Statue Approach) and conceptual approach (Conceptual Approach).